Partners in Prosperity: Strategic Industries for the U S and Japan - Julian Gresser; GRESSER (Julian) (New York McGraw Hill Book Company, 1984)
Gresser, a lawyer who has practiced in both the U.S. and Japan, argues that technology's crucial contribution to economic growth means that government must actively foster certain industries. He develops a method of identifying strategic industries and technologies, and a negotiation process to help the U.S. allocate resources to strategic sectors. Finally, Gresser urges that the United States and Japan pursue joint economic growth "as though their respective strategic industries were actually those of one country." With its many new insights and startling ideas, this book will profoundly influence American economic thinking for years to come.
Keywords: International Economics; Japanese Challenge; U S Japan Technological Partnership